2012
DOI: 10.1016/j.jacc.2012.01.070
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Response to Antiarrhythmic Drug Therapy Is Modulated by a Common Single Nucleotide Polymorphism in Atrial Fibrillation

Abstract: Objectives This study tested the hypothesis that response to antiarrhythmic drugs (AADs) is modulated by 3 common loci associated with atrial fibrillation (AF). Background Recent genome wide association studies (GWAS) have identified 3 loci, on chromosomes 4q25 (near PITX2), 16q22 (in ZFHX3), and 1q21 (in KCNN3), that associate with either typical or lone AF. These findings indicate that variable mechanisms contribute to AF susceptibility, and suggest that response to therapy may be genotype-dependent. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
87
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(95 citation statements)
references
References 33 publications
4
87
0
4
Order By: Relevance
“…It should be noted that recent works have hypothesized that the response to antiarrhytmic drug therapy is influenced by a common polymorphism on chromosome 4q25 near PITX2 gene [37] and that the risk of proarrhythmic effect is modulated by common variants in nitric oxide synthase 1 adaptor protein [38], thus explaining the patient-to-patient variations in response and proarrhtmic effect.…”
Section: Drug Namementioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that recent works have hypothesized that the response to antiarrhytmic drug therapy is influenced by a common polymorphism on chromosome 4q25 near PITX2 gene [37] and that the risk of proarrhythmic effect is modulated by common variants in nitric oxide synthase 1 adaptor protein [38], thus explaining the patient-to-patient variations in response and proarrhtmic effect.…”
Section: Drug Namementioning
confidence: 99%
“…Only study with head-to-head comparison of dronedarone with active control, better tolerability, lower efficacy PALLAS (2011) [36] 3236 Permanent AF (> 6 months), age > 65 years; additional cardiovascular risk factor 3,5 months Prematurely halted for increased primary cardiovascular endpoints HESTIA (2012) [37] 112 Paroxysmal AF; AF burden > 1%, dualchamber pacemaker with AF detection 12 weeks Reduction of AF burden by 59%…”
Section: Monthsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the rationale that the multiple genetic variants associated with AF might indicate variable mechanisms contributing to AF susceptibility, or variable sub-types of AF, Parvez et al (11) hypothesized that response to AAD therapy might also be genotype-dependent. Testing first in a discovery cohort of 478 patients, the authors identified an association between a response to AAD therapy and the rs10033464 SNP, but not with the other SNPs tested.…”
mentioning
confidence: 99%
“…Certain variations of these genes will alter the metabolism of warfarin, subsequently the dose requirement of warfarin [7,8]. Similarly, the SNP of cardiac ionic channel genes has been associated with the susceptibility to different arrhythmias including AF and the efficacy of antiarrhythmic drugs [9][10][11]. It is possible that patients carrying an AF-predisposing polymorphic genetic variation are more likely to develop AF compared to the "non-carriers" after taking a specific drug.…”
Section: Mechanism Of Drug-induced Afmentioning
confidence: 99%